Geochemistry of mid- upper eocene intra-continental alkaline volcanic range, south part of central alborz mountains, north of Iran. (Nexo Revista Científica, 2020)
The Ziaran volcanic Belt (ZVB), North of Iran contains a number of intra-continental alkaline volcanic range situated on South part of central Alborz Mountains, formed along the localized extensional basins developed in relation with the compressional regime of Eocene. The mid-upper Eocene volcanic suite comprises the extracted melt products of adiabatic decompression melting of the mantle that are represented by small volume intra-continental plate volcanic rocks of alkaline volcanism and their evaluated Rocks with compositions representative of mantle-derived, primary (or near-primary) melts. Trace element patterns with significant enrichment in LILE, HFSE and REEs, relative to Primitive Mantle. Chondrite-normalized of rare earth elements and enrichment in incompatible elements and their element ratios (e. g. LREE/HREE, MREE/HREE, LREE/MREE) shown these element modelling indicates that the magmas were generated by comparably variable degrees of partial melting of garnet lherzolite and a heterogeneous asthenospheric, OIB mantle sources.